2009
DOI: 10.1142/s0192415x09006953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Linkage Disequilibrium SNPs from a Kidney-Yang Deficiency Syndrome Pedigree

Abstract: In order to probe the genetic traits of Kidney-yang Deficiency Syndrome (KDS), we employed a national standard of KDS diagnosis for the collection of KDS subjects. Each candidate KDS subject from a typical family was diagnosed by 5 independent physicians of Traditional Chinese Medicine (TCM), and repeated for 3 years, all on the first Saturday of December. Fifteen samples of genomic DNA were isolated and genotyped by Affymetrix 100 K arrays of single nucleotide polymorphism (SNP). Then appropriate tools were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…Parallel correlation between the SNPs and ZHENG showed that the SNPs in the functional region (such as the UTR and near region) regulating the gene expression were the most closely related to ZHENG. This is consistent with previous literature [39, 41, 46]. These results suggest that the transcription and regulation of many genes are involved in the formation of ZHENG.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Parallel correlation between the SNPs and ZHENG showed that the SNPs in the functional region (such as the UTR and near region) regulating the gene expression were the most closely related to ZHENG. This is consistent with previous literature [39, 41, 46]. These results suggest that the transcription and regulation of many genes are involved in the formation of ZHENG.…”
Section: Discussionsupporting
confidence: 94%
“…With the improvement of SNP genotyping technologies, a variety of different SNP typing protocols are available for researchers [38]. Several studies have shown that TCM syndromes are associated with gene SNPs, for example the serotonin transporter gene polymorphism and excess of liver yang syndrome [39], ABCA1 gene polymorphism and phlegm syndrome and blood stasis syndrome in coronary heart disease [40], kidney- yang deficiency syndrome and linkage disequilibrium SNPs [41], liver Qi stagnation syndrome and gene polymorphism of tryptophan hydroxylase and G-protein β 3 submission in HBC patients [42], AT1R gene polymorphism and ZHENG in essential hypertension [43], and some cytokine gene ( TNFA , TGFB1 , and IL10 ) polymorphisms and TCM syndromes in hepatitis B cirrhosis patients [4446]. However, there are few studies on the relationship between genetic susceptibility and GC ZHENG.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that a part of TCM syndrome has the genetic [63, 64], proteomic [65, 66], and metabolomic [67, 68] basis according to such constitution classification, which is closely correlated with syndrome types. We need to make full use of achievements in modern science and technology to establish Zheng model according to TCM theory, which will be helpful to reveal the essence of TCM syndrome and to promote theoretical creativity.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Therefore, applying the advanced microarray and sequencing techniques can help clarify the biological basis of TCM syndrome (Xue et al, 2006). By using the microarray, RT-PCR and ELISA technologies, it was explored that Shen Yang deficiency syndrome is involved in special SNP linkage disequilibrium (LD) in the intragenic level (Ding et al, 2009b), and the marked low level of energy output in Shen Yang deficiency syndrome may be primarily attributed to the insufficient activity of the MAPK pathway (Ding et al, 2009a). The correlation of The correlation can be applied either between TCM symptoms (including tongue appearance and pulse feeling) and biological parameters in biomedicine, or between TCM syndrome (assemblages of clinical manifestation) and omics parameters/biomarkers in biomedicine.…”
Section: Syndrome Differentiation and Modern Research In Tcm Diagnosismentioning
confidence: 99%